Benchmark Framework for Mobile Robots Navigation Algorithms - Muñoz-Ceballos, Nelson David; Valencia-Velásquez, Jaime Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Despite the wide variety of studies and research on mobile robot systems, performance metrics are not often examined. This makes difficult to establish an objective comparison of achievements. In this paper, the navigation of an autonomous mobile robot is evaluated. Several metrics are described. These metrics, collectively, provide an indication of navigation quality, useful for comparing and analyzing navigation algorithms of mobile robots. This method is suggested as an educational tool, which allows the student to optimize the algorithms quality, relating to important aspectsof science, technology and engineering teaching, as energy consumption, optimization and design.